2012
DOI: 10.1093/jxb/ers271
|View full text |Cite
|
Sign up to set email alerts
|

N-fertilization has different effects on the growth, carbon and nitrogen physiology, and wood properties of slow- and fast-growing Populus species

Abstract: To investigate how N-fertilization affects the growth, carbon and nitrogen (N) physiology, and wood properties of poplars with contrasting growth characteristics, slow-growing (Populus popularis, Pp) and fast-growing (P. alba×P. glandulosa, Pg) poplar saplings were exposed to different N levels. Above-ground biomass, leaf area, photosynthetic rates (A), instantaneous photosynthetic nitrogen use efficiency (PNUE i), chlorophyll and foliar sugar concentrations were higher in Pg than in Pp. Foliar nitrate reducta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(96 citation statements)
references
References 40 publications
8
86
2
Order By: Relevance
“…Inorganic phosphate (Pi) is a prerequisite for RuBP and also a competitive inhibitor of RUBP [45,46]. Additionally, there was a strong correlation between K concentrations and Rubisco [21]. Zorb et al (2014) also reported that rates of photosynthesis were positively correlated with application rates of K [47].…”
Section: Discussionmentioning
confidence: 99%
“…Inorganic phosphate (Pi) is a prerequisite for RuBP and also a competitive inhibitor of RUBP [45,46]. Additionally, there was a strong correlation between K concentrations and Rubisco [21]. Zorb et al (2014) also reported that rates of photosynthesis were positively correlated with application rates of K [47].…”
Section: Discussionmentioning
confidence: 99%
“…NRT2;4 is a plasma membrane nitrate transporter that is expressed in shoot phloem in response to external nitrogen concentrations (Kiba et al, 2012;Li et al, 2012). Phosphate transporters (PHT1;4 and PHT3;3) are involved in phosphorus signaling and transport in Arabidopsis (Morcuende et al, 2007;Lei et al, 2011).…”
Section: The Coexpression Network Plays a Central Role In Transcriptomentioning
confidence: 99%
“…Quantitative reverse transcription (RT)-PCR of seven genes (for primer information, see Supplemental Table S8) was performed according to Li et al (2012). The reference gene was 18S ribosomal RNA (Supplemental Table S8).…”
Section: Validation Of Microarray Analysis By Quantitative Rt-pcrmentioning
confidence: 99%
“…The fast-growing ones possess greater N and P use efficiencies and higher enzymatic activities related to N assimilation and P mobilization (Gan et al, 2015). The fast-growing broadleaved tree Populus alba  P. glandulosa is more sensitive to increasing N availability (Li et al, 2012), while the slowly growing P. popularis is more sensitive to decreasing N availability (Luo et al, 2013b). Also, fast growing P. deltoides females are more sensitive to inorganic nitrogen forms than the slow growing male trees .…”
Section: Introductionmentioning
confidence: 99%